1998
DOI: 10.1038/sj.mp.4000405
|View full text |Cite
|
Sign up to set email alerts
|

Large CAG/CTG repeats are associated with childhood-onset schizophrenia

Abstract: Recent studies have shown an association between trinucleotide repeat expansions (TREs) and adult-onset schizophrenia (AOS). Childhood-onset schizophrenia (COS) is a severe variant of schizophrenia with onset of symptoms before age 12 years. We have used the repeat expansion detection (RED) method to investigate the occurrence of repeat expansions in a group of well-characterized COS patients as well as a set of clinically related childhood-onset psychosis cases labeled 'multidimensionally impaired' (MDI). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

1999
1999
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 27 publications
0
16
0
1
Order By: Relevance
“…Such studies have shown increased sizes of ligation products in schizophrenics, but there is large overlap between the product sizes in schizophrenics and normals, and the differences are not specific to schizophrenia [Morris et al, 1995;O'Donovan et al, 1996;Bowen et al, 1996;Gaitonde et al, 1997;Speight et al, 1997;Vincent et al, 1998;Burgess et al, 1998;Laurent et al, 1998;Li et al, 1998a;Martorell et al, 1999]. Studies of trinucleotide repeats in known genes have been disappointing.…”
Section: The Putative Loci: What Are We Looking For?mentioning
confidence: 93%
“…Such studies have shown increased sizes of ligation products in schizophrenics, but there is large overlap between the product sizes in schizophrenics and normals, and the differences are not specific to schizophrenia [Morris et al, 1995;O'Donovan et al, 1996;Bowen et al, 1996;Gaitonde et al, 1997;Speight et al, 1997;Vincent et al, 1998;Burgess et al, 1998;Laurent et al, 1998;Li et al, 1998a;Martorell et al, 1999]. Studies of trinucleotide repeats in known genes have been disappointing.…”
Section: The Putative Loci: What Are We Looking For?mentioning
confidence: 93%
“…The samples were split and analysed for both genders separately using M-W to determine whether a sex effect was present, as has been reported in several previous studies. 9,29 No significant differences in distribution were seen between male affecteds and matched controls, female affecteds and matched controls, male vs female affecteds or male vs female controls (P Ͼ 0.05). No significant correlations were observed with age or age-of-onset.…”
Section: Redmentioning
confidence: 93%
“…Given the high frequencies of large alleles at SEF2-1B and ERDA1 in our affected and control populations as well as others, [23][24][25]27 such high frequencies are likely the case in other studies which have reported significant increases in CAG/CTG repeat distribution amongst affected individuals. [6][7][8][9]11,29 A recently published study has reported weak evidence of association of large repeats at SEF2-1B (but not ERDA1) with BPAD. 30 Our findings in this study contradict this.…”
Section: Discussionmentioning
confidence: 99%
“…Of 8 studies examining bipolar disorder, 4 reported an association between bipolar disorder and longer CAG repeats, [194][195][196][197] while another 4 did not find a significant association. [198][199][200][201] In schizophrenia, an association with long CAG repeats was found in 3 studies 194,202,203 but not in 7 others. [198][199][200][204][205][206][207] Two CAG expansions that occur frequently in the normal population, located in an intron of the SEF2-1 gene on chromosome 18 181 and in the ERDA1/Dir1 locus on chromosome 17,208,209 are now known to account for most of the long CAG repeats detected by RED.…”
Section: Attempts To Detect Trinucleotide Repeat Expansion In Psychiamentioning
confidence: 95%